If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(y+2)+y=4(y-1)=10
We move all terms to the left:
3(y+2)+y-(4(y-1))=0
We add all the numbers together, and all the variables
y+3(y+2)-(4(y-1))=0
We multiply parentheses
y+3y-(4(y-1))+6=0
We calculate terms in parentheses: -(4(y-1)), so:We add all the numbers together, and all the variables
4(y-1)
We multiply parentheses
4y-4
Back to the equation:
-(4y-4)
4y-(4y-4)+6=0
We get rid of parentheses
4y-4y+4+6=0
We add all the numbers together, and all the variables
10!=0
There is no solution for this equation
| -9=-5b+2b | | 60=x^2+10x | | 7x+12=2(3) | | 18+x/5=4 | | 4=-5+3y | | z÷8+5=6 | | 5/15=3v | | 8(w-2)=-6w+12 | | 4=t+3t | | -9.6=y/3-2.1 | | a-34=47 | | 4x=7=-29 | | 5/7x+5=10 | | t÷5-2=10 | | 7^x=412 | | 6x-15+x+19.5=180 | | -20x+10=-6+-12x | | -6n=8 | | 51(x+4)=20(2x-1) | | 8x+3=8x+3=4.7x-(-2.8x-3.7)4.7x−(−2.8x−3.7) | | 8−3p=5 | | 2v+5v+2=12- | | x5=78 | | 23+y=56y= | | 83=-7+5n-5 | | -64x+42=-6x-22 | | 51(x+4)=57(2x-1) | | 2.5x=x+72 | | 12(x+1)=20(3x-2) | | -0.8(x-14)=24 | | 5x=x=72 | | 8m=3=59 |